Viewing Meaningful Work Through the Lens of Time - Tommasi, Francesco; Ceschi, Andrea; Sartori, Riccardo (Frontiers in Psychology, 2020)
Authors have paid considerable attention to how to define the meaningful work construct. This has led to providing comprehensive definitions in the light of different theoretical frameworks that reflect a degree of contestation within the field. Several of them have proposed definitions linked to the individuals’ pervasive sense of the value of their work. Others have offered descriptions centred on their temporal, episodic nature and emphasising the individual’s occasional work experience. These definitions reflected a potential temporal condition as well as the variety of time perspectives underpinning the authors’ conceptualizations of the construct. This paper conducted a broad literature review to analyse works which have adopted a temporal framework or supported a time-based definition of the construct. The analysis indicates two different conceptualizations of the construct: as a permanent/steady mindset and as a changeable/episodic experience. As a reflective paper, the present contribution develops an overall framework for views and theories on meaningful work. It reports a critical review on the matter to elevate understanding of meaningful work for further research and applied implications in work and organizational studies.